(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the concept of modern education, the concept of types of education, the uniqueness of primary education, the integration of education with the types of education, the connection of subjects in primary education, the word integration the dictionary meaning of , the content and essence of integrative education, the methods and tools of integrative education used in primary education, guidelines for their practical application, integrative education support for teachers and benefits for students, how pedagogues should use integrative learning in classes, complex thinking and its impact on the educational process, analytical thinking and its impact on students, critical thinking ability, increase in motivation, development of creativity, success of integrative education in teaching, development and upbringing of students, the formation of an understanding of the unity of their world, arousing students’ interest in education, and their desire to find unusual and new solutions to given tasks , innovative concepts in the educational process, imaginations within the system ensure that students know a whole range of subjects. (physical, chemical, biological, system of knowledge) is widely used in the field of knowledge, the described psychological evidence allows to determine the main features of the integration of primary, incomplete secondary and high school education.